Multi-arm polymers prepared by atom transfer radical polymerization (ATRP) and their electrospun films as oxygen sensors and pressure sensitive paints. (March 2019) - Shi, Jiayan; Zhou, Yifei; Jiang, Jiapei; Pan, Tingting; Mei, Zhipeng; Wen, Jiaxing; Yang, Cheng; Wang, Zijin; Tian, Yanqing
Graphical abstract: Highlights: Atom transfer radical polymerization was used for the first time to synthesize polymers for pressure sensitive paints. Multi-arm structured polymers were applied as pressure sensitive paints. Structure influence on sensing performance was observed. Electrospinning approach was used to generate microspheres and/or fibers for achieving high sensitivity. Abstract: New oxygen and pressure sensitive paints (PSPs) with four-arm polymeric structures were prepared by using a kind of controlled living polymerizations – atom transfer radical polymerization (ATRP). The polymers composing of poly(isobutyl methacrylate)- co -poly(trifluoroethyl methacrylate)s (PolyIBMA- co -PolyTFEM)s act as the matrices for the platinum porphyrin-based phosphorescence probes, which were copolymerized in the matrices. The polymers were characterized by using 1 H NMR, 19 F NMR, and GPC to demonstrate their successful preparation. The influence of polymer structures on sensing activity including the sensitivity and response time to oxygen and/or pressure was investigated. Results showed that copolymers with suitable compositions (hereinP3 ) can have highest sensitivity. Polymer structure's influence on response time to oxygen was also investigated. For increasing the polymer's surface area for further improving sensing sensitivity, electrospinning method was used for preparing films with micro-spherical or fibrous structures. The morphologies of electrospinning coated films were observed by SEM. Results showed that electrospinning coated films can respond much better to oxygen and pressure than their corresponding sprayed plates. This is the first time to apply the controlled living polymerization approach to prepare PSPs with multi-arm structures, which will broaden the PSP functional materials' design strategy.